2019
DOI: 10.1101/842666
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunocapture of dsRNA-bound proteins provides insight into tobacco rattle virus replication complexes and reveals Arabidopsis DRB2 to be a wide-spectrum antiviral effector

Abstract: 27 Plant RNA viruses form highly organized membrane-bound virus replication complexes 28 (VRCs) to replicate their genome and multiply. VRCs contain both virus-and host-encoded 29 proteins, and have been investigated through a number of experimental approaches, including 30 genetic screens on surrogate model experimental hosts and pull-down of viral replicase 31 proteins. Double-stranded RNA (dsRNA) is an obligate intermediate of the replication 32 process of all RNA viruses and is the trigger of potent antivi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 66 publications
(99 reference statements)
4
21
0
Order By: Relevance
“…To test if TBSV-BS3Ng replication is also associated to the production of spherules, we first infected N. benthamiana constitutively expressing the dsRNA-binding sensor protein B2:GFP [ 47 ]. Confocal and electron microscopy analyses of these plants confirmed that TBSV-BS3Ng replicates in association with severely modified peroxisomes containing numerous spherules ( Supplementary Figure S3 and [ 46 ]). Confocal and electron microscopy analyses of constitutively-expressing B2:GFP A. thaliana Col-0 plants infected with TBSV-BS3Ng ( Figure 2 ) revealed similar cytopathic structures than those observed in N. benthamiana ( Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…To test if TBSV-BS3Ng replication is also associated to the production of spherules, we first infected N. benthamiana constitutively expressing the dsRNA-binding sensor protein B2:GFP [ 47 ]. Confocal and electron microscopy analyses of these plants confirmed that TBSV-BS3Ng replicates in association with severely modified peroxisomes containing numerous spherules ( Supplementary Figure S3 and [ 46 ]). Confocal and electron microscopy analyses of constitutively-expressing B2:GFP A. thaliana Col-0 plants infected with TBSV-BS3Ng ( Figure 2 ) revealed similar cytopathic structures than those observed in N. benthamiana ( Supplementary Figure S3 ).…”
Section: Resultsmentioning
confidence: 91%
“…All A. thaliana lines used were previously described: drb2-1 , drb4-1 and drb2-1/drb4-1 [ 42 ]; dcl2-1 , dcl4-2 and dcl2-1/dcl4-2 [ 43 , 44 ]; ago2-1 [ 45 ] and ago1-27 [ 45 ]. The 35S: B2:GFP /Col-0 line was also previously described [ 46 ], as was 35S: B2:GFP / N. benthamiana [ 47 ]. A. thaliana were grown in a neon-lit chamber at 22–18 °C, 12 h/12 h light/dark photoperiod throughout the infection experiments, while N. benthamiana plants were grown in a greenhouse at 22–18 °C, 16 h/8 h light/dark photoperiod.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations